From peace education to culture of peace: context and issues - Guetta, Silvia (Studi sulla Formazione/Open Journal of Education, 2013)
The article wants to give some interpretive lines about theories and methodologies of peace education. The peace education is linked at the conflict and violent context and therefore there is not one and unique approach to study and to understand it how to plan research and projects on peace education. The article explains also how to insert within a broader meaning of culture of peace the peace education contribution. Today there is the awareness that every democratic education of quality must involve culture of peace with different approaches integrating human rights and development of mediation and nonviolent tools.